2017
DOI: 10.1021/acs.biochem.7b00131
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Genetic Code of a Photoautotrophic Organism

Abstract: The photoautotrophic freshwater cyanobacterium Synechococcus elongatus is widely used as a chassis for biotechnological applications as well as a photosynthetic bacterial model. In this study, a method for expanding the genetic code of this cyanobacterium has been established, thereby allowing the incorporation of unnatural amino acids into proteins. This was achieved through UAG stop codon suppression, using an archaeal pyrrolysyl orthogonal translation system. We demonstrate incorporation of unnatural amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Recently, our team reported the genetic code expansion of Synechococcus sp. PCC7942 ( syn 7942) cyanobacteria (Chemla et al, ), where we have reported our ability to site‐specifically incorporate unnatural amino acids (UAAs) into GFP. In this study, we have developed and demonstrated the ability to incorporate a UAA into an endogenous protein that takes part in both photosynthesis and respiration in syn 7942.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our team reported the genetic code expansion of Synechococcus sp. PCC7942 ( syn 7942) cyanobacteria (Chemla et al, ), where we have reported our ability to site‐specifically incorporate unnatural amino acids (UAAs) into GFP. In this study, we have developed and demonstrated the ability to incorporate a UAA into an endogenous protein that takes part in both photosynthesis and respiration in syn 7942.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to To date, live-cell imaging can be obtained through different approaches, however genetic code expansion, the reassignment of codons and incorporation of an unnatural amino acid (Uaa) into proteins 17 , displays advantages over other methodologies, and is gaining increasing exposure and momentum [18][19][20][21] . Genetic code expansion systems are being constantly improved, expanded and adapted to a growing number of organisms [22][23][24][25] . This technique aids in improving imaging.…”
Section: Mainmentioning
confidence: 99%
“…All plasmids for initial method establishment were constructed by a standard yeast assembly protocol 22 . The upstream and downstream regions from P. aeruginosa's leucyl translational system were chosen for OTS expression.…”
Section: Plasmids Constructionmentioning
confidence: 99%
“…Thereby enabling the rational enhancement of the chemical and physical properties of proteins. This methodology was established in the early years of the current century in E. coli [1] and gradually was adapted to many other organisms in both eukarya [2][3][4][5][6][7] and prokarya [8,9].…”
Section: Introductionmentioning
confidence: 99%